Peningkatan Kompetensi Guru Binaan dalam Menyusun RPP melalui Bimbingan Berkelanjutan di SMKN 4 Lhokseumawe - Ismail, Muhammad Yusuf (Jurnal Paedagogy, 2021)
This study aims to analyze the improvement of the teacher's ability in preparing Learning Implementation Plans (RPP) through continuous guidance at SMKN 4 Lhokseumawe with the instruments that have been prepared, namely in the form of observation sheets/observations of RPP components in accordance with Permendikbud No. 22 of 2016. This research method used school action research which is carried out for 3 months with two cycles. The subjects were 24 teachers. The research instruments were observation sheets, questionnaire, and interview guidelines. The data were analyzed by qualitative descriptive analysis. The result showed that coaching could improve the teachers’ ability in designing lesson plan at SMKN 4 Lhokseumawe. The improvement of teacher competence through extensive supervision in the first and second cycles could be seen an increase in results. The average score in cycle 1 was 68,75 categorized moderate and the average score in cycle 2 was 85 categorized good where the improvement was 23, 64%. The capacity building in this study has proven that efforts to improve teachers’ ability in preparing lesson plan through extensive supervision at SMKN 4 Lhokseumawe have obtained satisfactory results.